Antifungal and immunomodulatory activity of a novel cochleate for amphotericin B delivery against Sporothrix schenckii - Batista-Duharte, A. [UNESP]; Lastre, M.; Romeu, B.; Portuondo, D. L. [UNESP]; Téllez-Martínez, D. [UNESP]; Manente, F. A. [UNESP]; Pérez, O.; Carlos, I. Z. [UNESP] (Elsevier, 2016)
Introduction: Sporotrichosis is an emergent subcutaneous mycoses caused by species of the Sporothrix schenckii complex. Amphotericin B (AmB) remains the main antifungal drug for the treatment of systemic infections, but its use is limited by toxicity reasons. AFCo3 is a novel cochleate containing detoxified LPS, which exhibits drug delivery and immunomodulating properties. Here, AFCo3 was used as the vehicle for AmB to evaluate the immunomodulatory and antifungal efficacy against S. schenckii in vitro and in vivo. Methods and results: The minimum inhibitory concentrations of AFCo3-AmB and AmB were 0.25 and 1 μg/mL respectively. The minimum fungicidal concentration was 0.5 μg/mL for AFCo3-AmB and 2 μg/mL for AmB. AFCo3-AmB was less cytotoxic than AmB for peritoneal macrophages, using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method and reduced the AmB-induced hemolysis in murine erythrocytes. AFCo3-AmB improved the intracellular killing of phagocytized yeast and it enhanced the in vitro production of IL-1β, TNF-α and NO in peritoneal macrophages. Moreover, AFCo3-AmB was more effective than AmB in reducing spleen and liver fungal burden after repeated (five days) intraperitoneal administration of 5 mg/kg of AmB, in a Balb/c model of systemic infection, associated to a significant induction of Th1/Th17 response. Finally, blood chemistry revealed that AFCo3-AmB did not cause changes suggestive of nephrotoxicity, such as increases in total proteins, albumin, creatinine and blood urea nitrogen that were caused by free AmB. Conclusions: AFCo3-AmB exhibited a significant immunomodulator action, reduced toxicity and improved antifungal action against S. schenckii, suggesting a potential use as AmB delivery for systemic sporotrichosis treatment.
Keywords: Amphotericin B; Antifungal activity; Cochleates; Immunomodulation; Sporothrix schenckii; Sporotrichosis